EFFICIENCY OF ORGANIZATIONAL STRUCTURES IN THE CONTEXT OF THE MODERN MANAGEMENT PARADIGM - TERESHCHENKO, Tetiana; LALUEVA, Nadiya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the main indicators and conditions for ensuring the efficiency of organizational structures in the context of the modern management paradigm. A number of general features of the modern management paradigm are described. Namely, flexibility and adaptability, human-centeredness, digitalization of society, strategic management, change management, customer focus, corporate social responsibility, leadership development and teamwork. The concept and types of organizational structures are characterized. It is stated that the choice of the type of organizational structure is influenced by a number of factors, including: strategy, mission, goals of the organization, functions to be performed, market niche in which the organization will operate, size of the organization, technology, specifics of activity, resource provision, etc.The scientific views of scientists on the definition of the concept of “efficiency” are systematized. The approaches to defining the concept of efficiency are considered, namely: resource, effective, target, systemic, selective. It is proposed to consider efficiency as a manifestation of various processes and actions for achieving exclusively managerial goals. It is emphasized that the concept of efficiency should be given not only quantitative (ratio of profit and resources expended), but also qualitative characteristics (measure of success of the organization, focus, etc.).The author summarizes three groups of performance indicators of organizational structures: by assessing the output results, by the content of the organizational structure, by the rationality of the organizational structure; indicators of hierarchical structure assessment, indicators of organizational structure functionality assessment.A number of principles of efficiency of organizational structures are defined: cost-effectiveness of the structure, optimality, efficiency, reliability. The basic requirements for building an effective organizational structure are highlighted. The conditions for achieving the efficiency of organizational structures in the context of the modern management paradigm are formed.
Keywords: efficiency; organizational structure; modern management paradigm; performance indicators